La finalidad interna de organismos naturales y la vida - Sylvia Susana Rodríguez Prieto (Claridades: Revista de Filosofía, 2015)
The teleological judgment was distinguished from aesthetics basically by the starting point that the subject facing objects judges. In this case the subject of some knowledge about them and not judge only from outward warns that in them. This implies that the reality of these objects takes on a different dimension and man can include it in their daily work and that may account for its usefulness. The purpose in the sense of intentionality shown in certain natural products stores an external relationship with man and with other products because their existence is based on the convenience of its manifestation in time and place. In natural bodies the purpose of nature is based on an organic relationship between the components that are forming together a whole and be organized.